Symptom Profile and Etiology of Delirium in a Referral Population in Northern India: Factor Analysis of the DRS–R98 - Mattoo, Surendra K; Grover, Sandeep; Chakravarty, Kaustav; Trzepacz, Paula T; Meagher, David J; Gupta, Nitin (The journal of neuropsychiatry and clinical neurosciences, 2012)
Delirium is understudied in developing countries, where there tends to be a lower proportion of older persons and comorbid dementia. The authors assessed 100 consecutive cases of DSM-IV delirium (patients' mean age: 44.4 [standard deviation: 19.4] years; mean DRS–R98 score: 25.6 [3.6]) referred to an adult Consultation–Liaison Psychiatry service in Northern India. Disturbances of attention, orientation, visuospatial ability, and sleep disturbance were the most frequent symptoms, followed by language, thought-process abnormality, and motor agitation. A three-factor solution was identified, representing domains for cognition, higher-order thinking, and circadian rhythm/psychosis. These domains can guide studies addressing the relationship between symptom profile, therapeutic needs, and outcomes and are consistent with core domains previously identified in other countries.